Historical thought in students entering primary teaching training schools: an epistemic study of writing (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
There is a widespread consensus in Education as to the relevance of developing historical thought (HT) not only in general terms, but also, and more specifically in those who will become teachers for children and young people. Despite the lack of a unified definition for HT, specialists agree on one point: HT results from a process of construction, and this makes it a subject for teaching. It is considered that writing, conceived as an epistemic tool, is a fundamental element to enhance this process while offering a privileged material support to feedback the construction of HT. In this line, and within the framework of the Master of Specific Didactics (Universidad Nacional del Litoral, Argentina), the thesis "The historical thinking of the students who enter the Primary Education teacher training: an approach to their study from an epistemic approach to writing" was developed. The work exposes the results of the research carried out and considers the relevance of the study of the HT and writing relationship in reference to the debates that the Specific Didactics and Teacher Training in the region are going through.
Keywords: historical thought; epistemic writing; teacher training